O auxílio emergencial de inclusão digital através do programa de assistência estudantil no Instituto Federal da Paraíba (IFPB) : uma alternativa ao ensino na pandemia da Covid-19? - Cruz, Mércia Rocha (2024)
The present work entitled “EMERGENCY AID FOR DIGITAL INCLUSION THROUGH THE STUDENT ASSISTANCE PROGRAM AT THE FEDERAL INSTITUTE OF PARAÍBA (IFPB): an alternative to teaching during the COVID-19 pandemic?” sought to investigate and analyze the process of implementing Emergency Aid for Digital Inclusion, in the Student Assistance Program at IFPB/Campus João Pessoa, in times of the Covid-19 pandemic. In addition to evaluating the implementation and development of digital inclusion as a public policy within the scope of PNAES following the COVID-19 pandemic, this study aimed to identify changes in the IFPB Student Assistance Program, João Pessoa campus, based on implementation of emergency aid for digital inclusion in the pandemic context (2020/2021), as well as understanding how emergency actions to aid digital inclusion contributed to the feasibility and guarantee of the right to education. The analysis was developed during the investigation process, establishing Historical-Dialetic Materialism as an interpretation criterion, considering that it analyzes the object based on its movement and its approaches to the dynamics of social reality. As a methodological strategy, this study falls within the scope of the qualitative and quantitative approach and exploratory research. To collect and analyze the data, bibliographical and documentary research techniques were used, which are based on the investigation of scientific productions on the subject, as well as carrying out a survey of notices, institutional regulations and other media materials published in the official campus communication channels between the years 2020 and 2023. In this way, it was possible to identify that the urgent demand for digital inclusion during the pandemic period as a tool to enable Non-In-Person Teaching Activities (AENPs) established at IFPB, highlighted a change in the Student Assistance paradigm. This change, because it presented itself abruptly, also exposed gaps in the operationalization of digital inclusion, of an emergency nature, along the lines of the National Student Assistance Program (PNAES, 2010). However, on the other hand, this movement indicated, to a certain extent, the relevance of aiding digital inclusion in enabling access to remote education in the context of the pandemic.